Willingness to Pay for Offsetting Carbon Programs by Vehicle Owners in Sunsari District, Nepal - Nepal, Lok Raj; Juan, Shi (The Initiation, 2014)
The objective of this study was to assess the willingness to pay (WTP) of vehicle owners for carbon offsetting programs. This study could potentially assist local governmental institutions to take further steps in environmental conservation programs. A contingent valuation method was used. Open-ended questionnaire surveys were conducted with 181 respondents. The results revealed that WTP was dependent on several demographic variables including educational level, occupation, gender, and residential area. However, only occupation and educational level significantly affected the WTP of the respondents. The total WTP was 600 NRs. DOI: http://dx.doi.org/10.3126/init.v5i0.10246 The Initiation 2013 Vol.5; 23-31